"Arts fairs are the new discos" : Poppositions 2013. - Haden-Guest, Anthony; Poppositions Brussel 2013 ([S.l.] : Poppositions, 2013)
Abilene ; 200x75 ; Actionfiels ; Zmiana, Bec ; Collectif P4 ; Document ; Fuori Campo ; Greylight Projects ; Les commissaires anonymes ; Not Yet ; Outlandish ; Ponyhof Gallery ; Prestige ; R.K. Projects ; Rossi Contemporary ; Sils ; Squid & Tabernacle ; Thankyouforcoming ; Void ; Whatspace
Brass, Brussels, 18 April - 21 April 2013
kunstcatalogus